Hospitalized prevalence and 5-year mortality for IBD: record linkage study. - Button, L; Roberts, SE; Goldacre, M; Akbari, A; Rodgers, SE; Williams, J (2010)
AIM: To establish the hospitalized prevalence of severe Crohn's disease (CD) and ulcerative colitis (UC) in Wales from 1999 to 2007; and to investigate long-term mortality after hospitalization and associations with social deprivation and other socio-demographic factors. METHODS: Record linkage of administrative inpatient and mortality data for 1467 and 1482 people hospitalised as emergencies for > or = 3 d for CD and UC, respectively. The main outcome measures were hospitalized prevalence, mortality rates and standardized mortality ratios for up to 5 years follow-up after hospitalization. RESULTS: Hospitalized prevalence was 50.1 per 100 000 population for CD and 50.6 for UC. The hospitalized prevalence of CD was significantly higher (P < 0.05) in females (57.4) than in males (42.2), and was highest in people aged 16-29 years, but the prevalence of UC was similar in males (51.0) and females (50.1), and increased continuously with age. The hospitalized prevalence of CD was slightly higher in the most deprived areas, but there was no association between social deprivation and hospitalized prevalence of UC. Mortality was 6.8% and 14.6% after 1 and 5 years follow-up for CD, and 9.2% and 20.8% after 1 and 5 years for UC. For both CD and UC, there was little discernible association between mortality and social deprivation, distance from hospital, urban/rural residence and geography. CONCLUSION: CD and UC have distinct demographic profiles. The higher prevalence of hospitalized CD in more deprived areas may reflect higher prevalence and higher hospital dependency.